School educational policy in Egypt: societal assessment perspective. Issue 1 (11th June 2019) - Zaki Ewiss, M.A.; Abdelgawad, Fatma; Elgendy, Azza
Abstract : Purpose: Educational policy is crucial to society. Its process is related to political, economic and cultural variables. Nevertheless, there is a paucity of research in the field of applied social sciences, about how educational policies help to achieve societal objectives and welfare. This study aims to assess the concept and features of school education in Egypt during 1990-2017. Design/methodology/approach: Secondary data were collected using governmental reports and educational institutional reports and assessed through specialized focus groups. Findings: Results showed that, despite the multiplicity of strategies to reform the educational system, achievements and outcomes of educational processes are modest, and the developmental status of Egypt is lower than that of other countries. Studying educational outcomes indicated that school-education suffered from the predominance of quantity over quality and a serious inability to meet requirements of new knowledge era. Originality/value: A novel future-oriented proposal for context, ethos and reforming aspects of educational policy will be suggested.